2013
DOI: 10.2175/106143013x13596524515861
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Metals Biosorption by Jatropha curcas Deoiled Cake: Equilibrium and Kinetic Studies

Abstract: The equilibrium sorption of Cr(VI) and Cu(II) from aqueous solution using Jatropha curcas deoiled cake, has been studied with respect to adsorbent dosage, contact time, pH, and initial metal concentration in batch mode experiments. Removal of Cu(II) by deoiled cake was greater than that of Cr(VI). The adsorbent chemical characteristics, studied by Fourier transform-infrared analysis, suggested that the presence of Cr(VI) and Cu(II) in the biomass influenced the bands corresponding to hydroxyl and carboxyl grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The results appear to be consistent with the pseudo-second-order equation. Jatropha curcas deoiled cake, according to Rawat et al (2013), can be employed as a more e cient biosorbent than other regularly used sorbents for clean-up of wastewater containing Cr 6+ and Cu 2+ due to the presence of carboxyl and hydroxyl functional groups in biomass as indicated by FTIR analysis and pseudo-second-order model evident from adsorption kinetics. Abdolali et al (2015) prepared and characterized a novel biosorbent from a mixture of tea waste, maple leaves, and mandarin peels to adsorb multi-metals such as Cd, Cu, Pb, and Zn ions from an aqueous medium due to the major role played by carboxylate groups as evidenced from the FTIR spectra.…”
Section: Bioenergy and Plantation Crops For Metal Biosorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results appear to be consistent with the pseudo-second-order equation. Jatropha curcas deoiled cake, according to Rawat et al (2013), can be employed as a more e cient biosorbent than other regularly used sorbents for clean-up of wastewater containing Cr 6+ and Cu 2+ due to the presence of carboxyl and hydroxyl functional groups in biomass as indicated by FTIR analysis and pseudo-second-order model evident from adsorption kinetics. Abdolali et al (2015) prepared and characterized a novel biosorbent from a mixture of tea waste, maple leaves, and mandarin peels to adsorb multi-metals such as Cd, Cu, Pb, and Zn ions from an aqueous medium due to the major role played by carboxylate groups as evidenced from the FTIR spectra.…”
Section: Bioenergy and Plantation Crops For Metal Biosorptionmentioning
confidence: 99%
“…Du et al (2016) regenerated biosorbent laden with Pb(II), Cd(II), and Cu(II) easily using EDTA-2Na solution and re-used up to four times with an equivalently high adsorption capacity.Copper ions bound on alkali-treated leave powder of Hevea brasiliensis were capable of desorbing at > 99% with 0.05 mol/L HCl, 0.01 mol/L HNO 3 , and 0.01 mol/L EDTA solutions (2008). J. curcas deoiled cake desorption studies conducted byRawat et al (2013) revealed that maximum metals Cr(VI) and Cu(II)-recovery was rst evident in HNO 3 , trailed by CH 3 COOH and HCl. Desorption study conducted byNag et al (…”
mentioning
confidence: 99%
“…Equilibrium sorption of Cu (II) from synthetic solution by Jatropha curcas deoiled cake was higher than Cr (VI) in terms of pH, adsorbent dosage, initial metal concentration and dosage time, which was best fitted by Freundlich isotherm model. Desorption involves the use of chemical reagents such as HNO 3 [ 83 ] or HCl [ 82 ] are used for maximum metal recovery. Activation of carbonized oil palm decanter cake (OPDC) exhibited higher adsorption capacities on Cu (II), Pb (II) and Zn (II), but was not found to be suitable for Cd (II) and Cr (VI) adsorption.…”
Section: Waste Valorizationmentioning
confidence: 99%
“…Batch mode experiments were carried on adsorbent dosage, contact time, pH, and initial metal concentration, from which to investigate the sorption of Cr (VI) and Cu (II) f rom aqueous solution using Jatropha curcas deoiled cake (Rawat et al 2013). The results suggested that J. curcas deoiled cake could be an efficient biosorbent for removing Cr (VI) and Cu (II).…”
Section: Heavy Metal Adsorptionmentioning
confidence: 99%